In Silico Evaluation of Cinnamaldehyde and Its Analogues as Potential Alpha-Glucosidase Inhibitors for Antidiabetic Therapy - Ahwan Ahwan; Muhtadi Muhtadi; Rima Munawaroh (LPPM Akafarma Sunan Giri Ponorogo, 2025)
Diabetes mellitus (DM) is a chronic disease that can impact the health and well-being of patients in the long term. According to the International Diabetes Federation (2025), DM sufferers in Indonesia numbered 20.4 million in 2024. This figure is expected to increase to 28.6 million in 2050, DM treatment by inhibiting the alpha-glucosidase receptor. Cinnamaldehyde compounds have antidiabetic activity. This in silico study aims to determine the potential of cinnamaldehyde compounds and their analogs against alpha-glucosidase receptors as antidiabetics. Data on cinnamaldehyde compounds and their analogs were collected through the PubChem database and the alpha-glucosidase structure from the PDB database with the code 3TOP. This study evaluated cinnamaldehyde and its six analogs using molecular docking simulations on alpha-glucosidase receptors with tools such as PyRx 0.8, AutoDockTools-1.5.6, and Biovia Discovery Studio 2024, as well as pharmacokinetic and toxicity predictions using the pkCSM web tools and Lipinski's Rule of Five. The Lipinski's Rule of Five prediction results indicate that acarbose does not meet Lipinski's criteria. In contrast, cinnamaldehyde and its derivatives meet these criteria. Docking analysis shows that acarbose (7.1 kcal/mol) has the highest binding affinity for α-glucosidase, but cinnamaldehyde and its analogs (6.0–6.4 kcal/mol) still exhibit strong interactions at the enzyme's active residues. The ADMET profile supports the potential of cinnamaldehyde as an antidiabetic candidate with a broader systemic action range and a better pharmacokinetic profile than acarbose.